Home Based Exercise Rehabilitation Programs to Prevent Physical Frailty and Hospitalization-Associated Disability - SAITOH, MASAKAZU; DAIDA, HIROYUKI; IWATSU, KOTARO; MORISAWA, TOMOYUKI; TAKAHASHI, TETSUYA; FUJIWARA, TOSHIYUKI (Juntendo Iji Zasshi = Juntendo Medical Journal, 2024)
Daily health management and exercise are important for staying healthy and avoiding the need for long-term care. However, it is not easy to maintain regular exercise. Therefore, exercise needs to be done efficiently. In recent years, due to the aging population and increasing severity of illness, older patients often experience a significant decline in physical function, even with minimal rest, which often interferes with their daily life after discharge from the hospital. Frailty not only affects ADLs, but also strongly influences prognosis, including the development of atherosclerotic disease and rehospitalization. This perspective is a summary of the 51st Metropolitan Public Lecture held on June 17, 2023, and discusses exercise-based rehabilitation programs that can be delivered at home to prevent physical frailty and avoid hospitalization-related disability.